Metal transfer and bead formation in plasma arc–based wire arc additive manufacturing with vertical wire feeding - Wang, Chong; Chen, Xin; Suder, Wojciech; Ding, Jialuo; Pardal, Goncalo; Williams, Stewart W. (Springer, 2025)
Wire arc additive manufacturing (WAAM) is suitable for building large-scale engineering structures with high deposition rates and relatively low costs. However, in a typical plasma transferred arc (PTA)–based WAAM process using an inclined wire and vertical torch, keyhole defects can occur due to the high arc pressure, and the process is sensitive to the wire-feeding position with respect to the workpiece. Therefore, in this study, a PTA-based WAAM process with a new configuration employing a vertical wire and an inclined plasma torch was investigated for the potential of mitigation of keyhole formation and improvement of process tolerance. In particular, detailed investigations were carried out on the metal transfer mechanisms and bead formation characteristics under various processing conditions. The results show that the new configuration significantly reduces the likelihood of keyhole formation compared with the conventional approach due to the changes in arc pressure and heat distribution. Systematic analysis reveals that process parameters, including wire feed speed, arc current, and plasma gas flow rate, strongly influence droplet transfer stability, melt pool dynamics, and final bead morphology, which offer guidance for future process optimisation.
Keywords: Directed energy deposition; Deposition rate; Bead formation; Keyhole behaviour; Metal transfer; 4014 Manufacturing Engineering; 40 Engineering; Industrial Engineering & Automation; 46 Information and computing sciences; 49 Mathematical sciences